Confidence-building and international agreement in cybersecurity - Lewis, James Andrew (2011)
Notes that although the global digital network has become the backbone of the world economy and a significant new venue for attack, there has been little progress in negotiation or dialogue in the context of international security. Makes recommendations for steps which would facilitate reaching agreement in the near term.